Caracterização geoambiental da bacia hidrográfica do Rio das Antas utilizando ferramentas de geoprocessamento - Borghetti, Alex (2006)
The main goal of this paper it is to characterize the geoenvironmental of the hydrographic basin in Antas River, which is located in the city of Cascavel PR. The total area it is 134.53 km², divided in 21% of urban area and 79% of rural area. During the collection, manipulation and presentation of all the data related to the usage of soil, geomorphology and the conservation of the water s bodies had been used: cartographic and geographic information system (GIS) and images of satellite with high space resolution. All the way the soil was capture from the satellite image the rural area it was captured in the internet and georeferenced through control points traced by GPS. All the outcome was produced by thematic maps where was possible analyze the quantity and visualized the detail. Related to geomorphology, the basin showed 74.2% of the area insert in level I and II (convex top and soft slope). Considering the used of soil in the urban area 73.0%, is being occupied for related urbanization level in the rural area, the agriculture with 80.3%. The verification of APP (Area of Preservation Permanent) the rural area has only 55.6% of the area was formed for gallery forest, the urban perimeter percent was reduce 25.5%. The shortage ambient confirmed the quantities of the legal reserve that have only 34.8% of the area was occupied for vegetation. Using those perimeters it was possible to evaluate the physic space of the basin hydrographic, helping the process of hydrous assets.